2022
DOI: 10.1155/2022/4691172
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Contrast-Enhanced Magnetic Resonance Imaging Enhancement in the Differential Diagnosis of Hepatocellular Carcinoma and Combined Hepatocellular Cholangiocarinoma

Abstract: Background The distinction between combined hepatocellular-cholangiocarcinoma (cHCC-CC) and hepatocellular carcinoma (HCC) before the operation has an important clinical significance for optimizing the treatment plan and predicting the prognosis of patients. Magnetic resonance imaging (MRI) has been widely used in the preoperative diagnosis and evaluation of primary liver malignant tumors. Purpose The aim is to study the value of preoperative clinical data and enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Cirrhosis detected by CECT is highly suggestive of HCC. In this study, we found that few at-risk patients with cHCC-CCA had a cirrhotic liver background due to the different origins of HCC and cHCC-CCA, which is similar to the findings of the latest studies [ 24 , 29 31 ]. Additionally, this study revealed that cHCC-CCA patients exhibited higher rates of nonrim APHE with a volume < 50%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cirrhosis detected by CECT is highly suggestive of HCC. In this study, we found that few at-risk patients with cHCC-CCA had a cirrhotic liver background due to the different origins of HCC and cHCC-CCA, which is similar to the findings of the latest studies [ 24 , 29 31 ]. Additionally, this study revealed that cHCC-CCA patients exhibited higher rates of nonrim APHE with a volume < 50%.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have evaluated the performance of imaging characteristics in differentiating cHCC-CCA and HCC in recent years [ 15 , 18 , 31 , 38 , 39 ]. The model developed in this study, which combined CECT features and CA 19-9 levels to distinguish cHCC-CCA, was put into a visual form as a nomogram and demonstrated a remarkable sensitivity of 93.3%, showing better performance than previous ones (ranging from 40 to 73.8% [ 15 , 18 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported in a small sample size study 22 that ultrasonic proteomics can better distinguish cHCC-CC from HCC than LI-RADS. Previous studies on these two types of tumors mostly used data from a single center with few samples and imaging features whose interpretation depends on clinical data and subjective judgment, 19 , 22 , 23 lacking universality and objectivity. With histopathological examination being the “gold standard” of preoperative diagnosis of cHCC-CC, there are some cases where the puncture is not in place or the collected samples are insufficient, leading to misdiagnosis of cHCC-CC as HCC.…”
Section: Introductionmentioning
confidence: 99%